Community Resilience Based on Faith Values: The Role of Social Institutions in Flood Risk Reduction - Nurharisyah Hasibuan; Ahmad Maulana Anshori; Ochi Aprila (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze how faith values, through community-based social organizations, contribute to flood risk reduction and strengthen community resilience, particularly in meeting basic food and clothing needs. This study stems from the phenomenon of increased community social vulnerability due to flooding, which not only causes physical damage but also disrupts household economic sustainability and access to basic needs. The study used a Participatory Rural Appraisal (PRA) approach, enabling communities to become key actors in identifying vulnerabilities, local resources, and adaptation strategies based on their lived experiences. The research findings indicate that food and clothing insecurity are at the core of the social vulnerability of flood-affected communities. In this context, faith values ​​serve as a normative foundation that encourages practices of solidarity, care, and material assistance through social institutions such as the Jemari Sekato NGO. This organization serves as a facilitator between community needs and support from the government and universities through cross-sectoral collaborative mechanisms. This study concludes that faith values ​​function not only as spiritual support but also as institutionalized social capital that strengthens community-based resilience. Therefore, disaster risk reduction requires participatory integration of material, social, and religious aspects to build a more adaptive and sustainable resilience system